1964
DOI: 10.1002/pol.1964.100020338
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular hydride shift polymerization by cationic mechanism. I. Introduction and structure analysis of poly‐3‐methylbutene‐1

Abstract: The low temperature cationic polymerization of 3‐methylbutene‐1 proceeds by intramolecular hydride shift mechanism. The secondary carbonium ion rearranges to a tertiary one prior to propagation. Thus the repeat unit of cationically obtained poly‐3‐methylbutene‐1 is not the expected or 1,2 structure but an α,α′‐dimethylpropane‐type 1,3 unit, e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1966
1966
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[24][25][26][27][28][29][30] Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3-type hydride shift to form a tertiary carbocation during each propagation step, yielding a gemdimethyl on every third carbon. They reported that if the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30] Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3-type hydride shift to form a tertiary carbocation during each propagation step, yielding a gemdimethyl on every third carbon. They reported that if the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…In related work conducted in the early 1960's, Kennedy and coworkers synthesized polyethlene with gem ‐dimethyl groups on every third carbon via a cationic polymerization of 3‐methyl‐1‐butene in the presence of aluminum chloride 24–30. Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3‐type hydride shift to form a tertiary carbocation during each propagation step, yielding a gem ‐dimethyl on every third carbon.…”
Section: Introductionmentioning
confidence: 99%
“…we obtain (II- 59) With these conditions the constant components of the envelopes B(t) and A(t) are, respectively, the absorption and dispersion signals, corresponding to the effective exciting field wlJo(f3) with amplitudes increased by a factor J o (f3). When {:J = 0, these expressions revert to the normal functions of v and u [see expression (I- 88)].…”
Section: Nonstationary Processesmentioning
confidence: 99%
“…From the relative intensity of the peaks of methyl and methylene protons of a polymer of 3-methylbutene-1 it was established [59] that the chain of the polymer consists of a-dimethylpropane units By treating germanium diiodide with acetylene and methylating the product with methylmagnesium iodide, Vol'pin and his coworkers [37] synthesized a polymer with alternating double bonds and germanium atoms in the chain. 'rhe NMR spectrum of a solution of the polymer contained only two peaks with a ratio of intensities of 1: 3 and chemical shifts reliitive to benzene of 0.3 • 10-6 and 7.0 • 10-6 • These peaks correspond to methyne and methyl protons, proving the structure of the polymer…”
Section: IIImentioning
confidence: 99%